SISTEM INFORMASI ADMINISTRASI DATA KEPENDUDUKAN DAN LAYANAN PUBLIK BERBASIS WEB - Putra, Roni Twiyoga Pramana; Anita, Anita; Widodo, Sugeng (DINAMIKA DOTCOM, 2018)
Population is a group of people that live in a particular area. The population data set required by the government to determine policies related to public services, development plans, budget allocations, democratic development and law enforcement. Therefore, the existence of every inhabitant should be noted and properly managed. Currently, the data management mechanism of the population involves many parties and is done gradually, starting from Rukun Tetangga (RT), Rukun Warga (RW), village and subdistrict office. some of the problems experienced by the village government are: residents are not aware of the terms of submission of public services, RT/RW is difficult to find or can only be encountered at certain times, the population took a long time to get a letter from the village government and village officials take a long time to report the status of the population. To overcome these problems, an integrated information system is needed. Through an integrated system, residents will get the information they need, the villages tools get the ease in providing services to the public and ease in the preparation of report.Â Keywords : Information system,Population, Public services, Administration